IMAGE OF SPAIN IN RUSSIA: PAST AND PRESENT - E. . Cherkasova (Ибероамериканские тетради, 2016)
The article is dedicated to the phases of formation of the image of Spain in Russia: romantic, prevailed until the early twentieth century, «Soviet» associated with the civil war, and modern, based on the development of political contacts and personal observations. The influence of political, economic and cultural factors on the formation of lasting representation of the country as well as on the stereotypes is considered.